Heavy metal in the culture of Brazilian media: the case of Black Sabbath and Fantástico television show (Comunicação & Inovação, 2015)
This paper presents a study of the discourseproduced in a news story broadcasted in theBrazilian television show Fantástico on RedeGlobo, on July 7th 2013, about the English heavymetal group Black Sabbath. Adopting a critical,historical and dialectical approach, this researchhas its theoretical-methodological approachbased on the assumptions of Douglas Kellner(2001) and Roland Barthes (1971). Amongthe main results, we found that Fantásticooperates in line with the globalizing marketideology using deviations such as fait divers.
Keywords: Media culture. Heavy metal. Fait divers.